Erratum: Morphology and star formation in IllustrisTNG: the build-up of spheroids and discs - Tacchella, Sandro; Diemer, Benedikt; Hernquist, Lars; Genel, Shy; Marinacci, Federico; Nelson, Dylan; Pillepich, Annalisa; Rodriguez-Gomez, Vicente; Sales, Laura V; Springel, Volker; Vogelsberger, Mark (Monthly notices of the Royal Astronomical Society, 2021)
This is an Erratum to the paper ‘Morphology and star formation in IllustrisTNG: the build-up of spheroids and discs’, which is published in MNRAS, 487, 5416-5440 (2019).In the original version of this paper, the spatial velocities of stellar particles had been incorrectly converted to peculiar velocity. Specifically, in order to obtain the peculiar velocity, instead of multiplying the spatial velocities by $\sqrt{a}$, we divided them by $\sqrt{a}$, where a is the scale factor of the universe. Since a = 1 at the present-day epoch, this has no impact on the results obtained at redshift z = 0. However, this mistake has important consequences at earlier cosmic times, which motivate this erratum.